Efficient Killing of Multidrug‐Resistant Internalized Bacteria by AIEgens In Vivo. Issue 9 (2nd March 2021) - Li, Ying; Liu, Fei; Zhang, Jiangjiang; Liu, Xiaoye; Xiao, Peihong; Bai, Haotian; Chen, Shang; Wang, Dong; Sung, Simon H. P.; Kwok, Ryan T. K.; Shen, Jianzhong; Zhu, Kui; et al.
Abstract: Bacteria infected cells acting as "Trojan horses" not only protect bacteria from antibiotic therapies and immune clearance, but also increase the dissemination of pathogens from the initial sites of infection. Antibiotics are hard and insufficient to treat such hidden internalized bacteria, especially multidrug‐resistant (MDR) bacteria. Herein, aggregation‐induced emission luminogens (AIEgens) such as N, N ‐diphenyl‐4‐(7‐(pyridin‐4‐yl) benzo [ c ] [1, 2, 5] thiadiazol‐4‐yl) aniline functionalized with 1‐bromoethane (TBP‐1) and (3‐bromopropyl) trimethylammonium bromide (TBP‐2) (TBPs) show potent broad‐spectrum bactericidal activity against both extracellular and internalized Gram‐positive pathogens. TBPs trigger reactive oxygen species (ROS)‐mediated membrane damage to kill bacteria, regardless of light irradiation. TBPs effectively kill bacteria without the development of resistance. Additionally, such AIEgens activate mitochondria dependent autophagy to eliminate internalized bacteria in host cells. Compared to the routinely used vancomycin in clinic, TBPs demonstrate comparable efficacy against methicillin‐resistant Staphylococcus aureus (MRSA) in vivo. The studies suggest that AIEgens are promising new agents for the treatment of MDR bacteria associated infections. Abstract : Aggregation‐induced emission luminogens (AIEgens) offer great potentials to track and dissect their modes of action in bacteria and pharmacokinetics processes in hosts. AIEgens serve as a novel class of antibiotics by triggering reactive oxygen species (ROS)‐mediated membrane damage and by activating mitochondria dependent autophagy to kill bacteria, which are promising adjuvants to boost mammalian cells for bacterial clearance and treatment of MRSA associated peritonitis.